2008
DOI: 10.1029/2007jc004408
|View full text |Cite
|
Sign up to set email alerts
|

Analytical description of tidal dynamics in convergent estuaries

Abstract: [1] Analytical solutions of the one-dimensional hydrodynamic equations for tidal wave propagation are now available and, in this paper, presented in explicit equations. For given topography, friction, and tidal amplitude at the downstream boundary, the velocity amplitude, the wave celerity, the tidal damping, and the phase lag can be computed. The solution is based on the full nonlinearized St. Venant equations applied to an exponentially converging channel, which may have a bottom slope. Two families of solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
267
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(274 citation statements)
references
References 20 publications
7
267
0
Order By: Relevance
“…Recently, Cai et al (2012a) proposed a new analytical framework for understanding the tidal damping in estuaries. They concluded that the main differences between the examined models (e.g., Savenije et al, 2008;Toffolon and Savenije, 2011;Kuijper and Van Rijn, 2011) lies in the treatment of the friction term in the momentum equation. Furthermore, Cai et al (2012a) presented a new "hybrid" expression for tidal damping as a Table 1.…”
Section: Analytical Hybrid Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Cai et al (2012a) proposed a new analytical framework for understanding the tidal damping in estuaries. They concluded that the main differences between the examined models (e.g., Savenije et al, 2008;Toffolon and Savenije, 2011;Kuijper and Van Rijn, 2011) lies in the treatment of the friction term in the momentum equation. Furthermore, Cai et al (2012a) presented a new "hybrid" expression for tidal damping as a Table 1.…”
Section: Analytical Hybrid Modelmentioning
confidence: 99%
“…It can be demonstrated that tidal hydrodynamics is controlled by three-dimensionless parameters that depend on localized geometry and external forcing (e.g., Toffolon et al, 2006;Savenije et al, 2008), i.e., ζ the dimensionless tidal amplitude (indicating the seaward boundary condition), γ the estuary shape number (representing the effect of crosssectional area convergence) and χ the friction number (describing the role of the frictional dissipation). These parameters are defined in Table 1, where η is the tidal amplitude and K s is the Manning-Strickler friction coefficient.…”
Section: Dimensionless Parameters Local Variable Dependent Variable Tmentioning
confidence: 99%
See 1 more Smart Citation
“…For a predominant tide (e.g. M 2 ), the phase lag is determined by ε = π − (φ Z − φ U ), in which φ Z and φ U represent the phase of water level and velocity, respectively (Savenije et al, 2008).…”
Section: Analytical Model For Tidal Hydrodynamicsmentioning
confidence: 99%
“…To explore the interaction between different constituents of the tidal flow, the quadratic velocity u|u| (where u is the velocity) is usually approximated by a truncated series expansion, such as a Fourier expansion (Proudman, 1953; z u h z Closed end Figure 1. Geometry of a semi-closed estuary and basic notation (after Savenije et al, 2008).…”
Section: Introductionmentioning
confidence: 99%